Clinical study of pancreatitis and its management - Nandu, Vipul V.; Deshpande, Amol V. (International Surgery Journal, 2016)
Background:Pancreatitis has been recognized since antiquity but the importance of pancreas and the severity of its inflammatory disorders were realized only in middle of 19th century. Pancreatitis by itself is a disease which is unique, protean and extrudes into the diagnostic arena. Objectives of the study was to study the demographic characteristics of pancreatitis, and to study the various etiological factors of pancreatitis, and to study the clinical presentation of pancreatitis and its management. Methods: Total 142 patients were enrolled over a period of 3 years for the study. Cases were studied with reference to clinical history and physical findings. Treatment was planned according to the severity of pancreatitis and presence or absence of complications with either conservative or surgical methods. Patients were followed up for 6 months to look for recurrence or complications developing after discharge. Results:92.25% patients were male. Highest incidence was noted in 20-40 years age group (mean- 38.94 years). More common among unskilled workers. Alcohol was the most common cause (78.17% patients). Abdominal pain and epigastric tenderness being the most common mode of presentation. Most of the patients were managed conservatively. Duration of hospital stay for most of the patients was 4 to 9 days. Fluid collection in abdomen was the most common complication of pancreatitis. Conclusions:Acute pancreatitis is a common cause of acute abdomen in patients presenting to the surgical emergency department. The management is mainly conservative with surgery limited to only a few selected cases, depending upon the severity of the disease.